PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN DALAM UPAYA MENINGKATKAN PENGENDALIAN INTERNAL - Kholidah, Nur Diana; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to evaluate the role of sales accounting information system in order to improve the internal control which has been carried out by PT. Dimensi citra semesta which engages in the field of sales of medical equipment. The method has been carried out by using descriptive qualitative method and the data collection techniques have been done by performing observation, interviews, and documentation. The result of the research shows that sales accounting information system which have been applied by PT. Dimensi citra semesta has presented information which is required by the company accurately and correctly although there are still weaknesses which needs to be improved from the sales report is not sufficient due to the absence of sales reports per item of goods, sales per customer reports, and sales reports details. Overall, the internal control at PT. Dimensi citra semesta has been running adequate because it has met the elements of internal control.Keywords: Sales accounting information system, Internal control, Sales activity